High induction rate onto extended-release naltrexone for people with opioid use disorder: experiences from a Norwegian naturalistic study - Jon Mordal; Farid Juya; Line Holtan; John-Kåre Vederhus; Arild Opheim; Ida H. Brenna; Asle E. Enger; Bente Weimand; Kristin Klemmetsby Solli; Lars Tanum (Addiction Science & Clinical Practice)
Abstract Background For people with opioid use disorder (OUD), extended-release naltrexone (XR-NTX) is an effective antagonist treatment option. However, successful opioid tapering and abstinence is a prerequisite for XR-NTX induction and has repeatedly been reported as a major barrier to effective treatment. The aims of this study were to describe XR-NTX induction rates, reasons for incomplete induction, and extraordinary complications reported during the induction phase. We also compared sociodemographic and clinical variables among those who did and did not complete induction onto XR-NTX. Methods This naturalistic, multicenter, and open-label Norwegian study of XR-NTX included men and women aged 18–65 who had severe OUD. Most participants were referred to inpatient medically managed opioid withdrawal and received individualized pharmacological and psychosocial treatment according to clinical assessment and national guidelines. After opioid withdrawal, the participants underwent a minimum of three opioid-free days prior to XR-NTX induction. Variables were collected through baseline assessments and a retrospective patient chart review. XR-NTX induction completers and non-completers were compared via bivariate and logistic regression analyses. Results Of 129 participants with recent opioid use at inclusion, 106 (82%) completed XR-NTX induction. Induction was initiated in an inpatient setting for 116 participants (90%) and extraordinary complications were noted for 19 (15%) patients. Withdrawal symptoms and ambivalence were the most common reasons for non-completion, each noted in 75% of the cases. As compared with those who successfully completed induction, non-completers more often reported lifetime hepatitis (78% vs. 52%, p = 0.017), had a longer period of current substance use (mean 119 vs. 54 months, p = 0.001), and more frequently used methadone prior to study inclusion (43% vs. 8%, p < 001). In logistic regression analyses, methadone use was the only significant factor and was negatively associated with completion (odds ratio 0.20, 95% confidence interval = 0.05–0.72, p = 0.014). Conclusion The results demonstrate the safety, efficacy and tolerability of a Norwegian opioid withdrawal and XR-NTX induction procedure. Although the present induction rate was high, our findings indicate that methadone users need special attention and tailored interventions regarding opioid withdrawal management and XR-NTX induction. Trial registration The study is registered at clinicaltrials.gov (NCT03647774).